Role of Asymmetrical Dimethylarginine in Diabetic Microvascular Complications. Issue 4 (October 2016) - Du, Mei-Rong; Ju, Gui-Xia; Li, Nian-Sheng; Jiang, Jun-Lin
Abstract : Abstract: Microvascular complications are the leading causes of acquired blindness, end-stage renal failure, and varieties of neuropathy associated with diabetes. Asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase inhibitor, is involved in endothelial dysfunction, oxidative stress, and inflammation associated with the progression of diabetic microvascular complications. Elevated ADMA has been detected in experimental animals and patients with diabetic microangiopathy like retinopathy, nephropathy, and neuropathy. In the review, we focus on the role of ADMA in the pathobiology of major microvascular complications of diabetes.